Deer density and plant palatability predict shrub cover, richness, diversity and aboriginal food value in a North American archipelago. Issue 12 (11th September 2014) - Arcese, P.; Schuster, R.; Campbell, L.; Barber, A.; Martin, T. G.; Bradley, Bethany
Abstract Aim Trophic cascades are a common consequence of herbivore outbreak and in the absence of hunting can cause the local extinction of native plant species and communities. We compared plant communities at 66 island and mainland sites to test the hypothesis that deer (Cervidae) determine species cover, richness and diversity and that palatable species become rare at high deer density. We validate a region‐wide index of deer density and impact on plant communities in a region where culturally significant food plants maintained by aboriginal people prior to European contact helped to define baseline plant communities. Location Gulf and San Juan Island archipelagos and North American mainland. Methods We conducted surveys of 49 native, 10 exotic and 15 culturally significant plant species and deer sign at 66 sites on 35 islands and mainland to determine deer abundance and plant species cover, richness and diversity. We identified culturally significant food plants facilitated by aboriginal people using ethnobotanical knowledge, quantified plant palatability via cafeteria trials and characterized shrub architecture. Results Native and culturally significant shrub cover, richness and diversity were 52–85% lower at sites with abundant deer (0.9–2.8 ha−1) versus no deer. However, these values were also 38–82% lower at sites in the lowest deer density class (< 0.08 ha−1) versus sites with no deer present. Palatable cover was 92% lower where deer were abundant versus absent and 28% lower in low‐density versus deer‐free sites. Shrub architecture provided an easily applied index of native and culturally significant plant cover and deer density. Main conclusions We provide comparative examples of endangered plant communities to demonstrate that, contrary to the intermediate disturbance hypothesis, any positive effect of deer on plant diversity on islands in the Pacific north‐west of North America occurs at densities < 0.08 ha−1, if at all. This detailed example of trophic downgrading highlights the need and provides the methods to identify herbivore densities compatible with the persistence of all native species in conserved landscapes.